How Do Healthcare Professionals Perceive Continuous Professional Development? A Cross-Sectional National Study from Jordan - Younes, Nidal; Ababneh, Anas; Alshraideh, Hussam; AbuAlRub, Raeda; Qanno', Omar; Gharaibeh, Muntaha (Jordan Medical Journal, 2026)
Background: Continuous professional development is essential to enhance the knowledge and competency of healthcare professionals. However, no previous research from Jordan assessed the perception of healthcare professionals about continuous professional development. Objective: This research aimed to investgate the perception of healthcare professionals about continuous professional development in Jordan. Methods: A cross-sectional study was conducted in the period between December 2017 till April 2018 in multiple healthcare settings in Jordan. The perception of 2,204 healthcare professionals including physicians, dentists, pharmacists, nurses, and allied healthcare professionals was investigated using a structured self-reported questionnaire. Assessment of perception included the perceived preferences and expected benefits of continuous professional development activities. Results: The most preferred continuous professional development activity was journal/internet reading activity, while research-based activity was the least preferred. Journal/internet reading activity was significantly preferred activity in the private sector (p=0.04). There was a significant difference in all the studied preferred continuous professional development activities between different HCPs (all p<0.05). The most perceived expected benefit of continuous professional development was enhanced knowledge while satisfying learning ambitions was the least. There was a significant difference in the expected benefits among health sectors and this included improving patients’ outcomes, improving personal skills, and enhancing personal knowledge (all p<0.05). There was also a significant difference in the expected benefits among healthcare professionals and this included improving the satisfaction of patients and their families, improving the clinical outcomes of patients, changing the current clinical practice, improving personal skills, and enhancing personal knowledge (all p<0.05). Conclusions: The perception of continuous professional development is varied between different HCPs and health sectors in Jordan. Future measures to design an effective continuous professional development for Jordanian HCPs should consider this variation.